In vivo bioactivity assessment on Epilobium species: A particular focus on Epilobium angustifolium and its components on enzymes connected with the healing process - Karakaya, Songul; Suntar, Ipek; Yakinci, Omer Faruk; Sytar, Oksana; Ceribasi, Songul; Dursunoglu, Benan; Guvenalp, Zuhal (Elsevier Ireland Ltd, 2020)
Ethnopharmacological relevance: Epilobium species are generally known as Yaku Otu in Turkey, which mens plaster herb in English. Young shoots of Epilobium angustifolium L., Epilobium stevenii Boiss., and Epilobium hirsutum L. are consumed as salad or meal. These species have been used as a poultice for the treatment of mouth wounds in traditional medicine. An ointment prepared from leaves is used for skin disorders in children. Aim of the study: We aimed to evaluate the ethnopharmacological use of Epilobium angustifolium, E. stevenii, and E. hirsutum by using in vivo and in vitro experimental models, and to identify the active wound-healer compound (s) and to explain the probable mechanism of the wound-healing activity. Materials and methods: Evaluation of wound healing effects of plant extracts was performed in rats and mice by linear incision and circular excision wound models. Determination of total phenolic constituents and antioxidant capacities, which are known to promote the wound healing process, were carried out through Folin-Ciocalteau method and 2,2 Diphenyl 1 picrylhydrazyl (DPPH) scavenging assay as well as determination of total antioxidant status (TAS) and total oxidant status (TOS) on the treated tissues. The active ethyl acetate (EtOAc) sub-extract of E. angustifolium was fractionated by different chromatographic separation techniques. The structures of isolated compounds were elucidated via detailed analyzes (NMR and LC/MS). In addition, in vitro collagenase, hyaluronidase, and elastase enzymes inhibitory activity tests were performed on the isolated compounds to discover the activation pathways of the samples. Results: Among the methanol (MeOH) extracts, E. angustifolium had the highest wound healing activity. Among the sub-extracts, EtOAc showed the highest wound healing activity. Thus, EtOAc sub-extract was subjected to chromatography to isolate the active compounds. Five known flavonoids namely hyperoside (quercetin-3-O-13-Dgalactoside) (1), kaempferol (2), kaempferol-3-O-alpha-L-rhamno pyranoside (3), quercetin-3-O-alpha-L-rhamno pyranoside (4), and quercetin-3-O-alpha-L-arabino pyranoside (5) were isolated from the EtOAc sub-extract of E. angustifolium. In vitro tests showed that hyperoside could be the compound responsible for the wound-healing activity by its significant anti-hyaluronidase, anti-collagenase, and antioxidant activities. Conclusion: The EtOAc sub-extract of the aerial part of Epilobium angustifolium displayed remarkable wound healing activity with anti-hyaluronidase, anti-collagenase, and antioxidant activities. Hyperoside was detected as the primary active compound of the aerial parts. According to the results, we suggest that EtOAc sub-extract of E. angustifolium and hyperoside may be a potent nominee to be used for the improvement of a wound-healing agent.
Keywords: Antioxidant; Epilobium; Flavonoid; Hyperoside; Wound healing